2007
DOI: 10.1111/j.1471-4159.2007.04746.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of cyclin‐dependent kinase 5 by calpains contributes to human immunodeficiency virus‐induced neurotoxicity

Abstract: Although the specific mechanism of neuronal damage in human immunodeficiency virus (HIV) -associated dementia is not known, a prominent role for NMDA receptor (NMDAR)-induced excitotoxicity has been demonstrated in neurons exposed to HIV-infected/activated macrophages. We hypothesized NMDAR-mediated activation of the calcium-dependent protease, calpain, would contribute to cell death by induction of cyclin-dependent kinase 5 (CDK5) activity. Using an in vitro model of HIV neurotoxicity, in which primary rat co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
91
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(100 citation statements)
references
References 106 publications
7
91
1
Order By: Relevance
“…87,88 This, in turn, could activate calpain cleavage of p35 into p25 and result in abnormal activation of CDK5. 36 This is consistent with the proposed neurotoxic mechanism of abnormal CDK5 activation in AD, 37,38 and with studies in the brains of HIV patients and in primary neurons treated with conditioned media from HIV-infected macrophages showing NMDAR-dependent activation of p25/CDK5. 36 In agreement with a role for aberrant CDK5 activation in neurodegeneration in HIV models, a previous in vitro study by Wang et al 36 showed that treatment with the CDK5 inhibitor roscovitine protected primary neurons from the neurotoxic effects of HIV-infected monocytederived macrophages.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…87,88 This, in turn, could activate calpain cleavage of p35 into p25 and result in abnormal activation of CDK5. 36 This is consistent with the proposed neurotoxic mechanism of abnormal CDK5 activation in AD, 37,38 and with studies in the brains of HIV patients and in primary neurons treated with conditioned media from HIV-infected macrophages showing NMDAR-dependent activation of p25/CDK5. 36 In agreement with a role for aberrant CDK5 activation in neurodegeneration in HIV models, a previous in vitro study by Wang et al 36 showed that treatment with the CDK5 inhibitor roscovitine protected primary neurons from the neurotoxic effects of HIV-infected monocytederived macrophages.…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with recent studies showing that aberrant activation of the CDK5 7,36 and GSK3␤ 7,[33][34][35]58 signaling pathways contribute to the neurodegenerative pathology in patients with HIV-associated neurocognitive impairment. Although a previous study focused on the role of p35 and CDK5 activation via the N-methyl-D-aspartate receptor (NMDAR), 36 the present study investigated the contribution of abnormal activation of this pathway to tau hyperphosphorylation in patients with HIVE. In patients with AD, abnormal activation of CDK5 and GSK3␤ have been implicated in the aberrant phosphorylation of tau and associated substrates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under these pathological conditions, calpain cleaves a number of neuronal substrates essential for neuron survival. For example, the neuron-specific activator of cyclin-dependent kinase 5 (cdk5), p35, is a well known calpain substrate (Kusakawa et al, 2000; M. S. Patzke and Tsai, 2002;Wang et al, 2007). The calpain-mediated cleavage of p35 to p25 is involved in the pathogenesis of Alzheimer's disease, and the calpainmediated p35 cleavage pathway may serve as a target for pharmacological intervention (Patrick et al, 1999; M. S. .…”
Section: Introductionmentioning
confidence: 99%